Effect of nonlinearity, magnetic and nonmagnetic impurities, and spin-orbit scattering on the nonlocal microwave response of a d-wave superconductor
By using linear response theory the low-temperature microwave response of a nonlocal and nonlinear d-wave superconductor with magnetic and nonmagnetic impurities is calculated. We will show that for the local, linear, and pure sample, penetration depth, Δλ(T), and conductivity, Δσ1(T), vary linearly with temperature, consequently the resistance, ΔR(T), would change linearly with temperature in agreement with experimental results and for the non-local, nonlinear sample the linear temperature dependences ΔR(T) change to quadratic function. For impure samples the nonlocality and nonlinearity effects are completely hidden by impurities and the temperature dependences Δλ(T) and Δσ1(T) are determined by temperature interval namely the ranges of T < T * and T *